Dealing with the Defecit: Are Tax Increases the Answer? (Tufts Archival Research Center, 2007)
Institute for Research on the Economics of Taxation economic report on the federal defecit. Finds that raising taxes is not the solution to the defecit problem. Accuses government policy makers of disregarding facts showing that raising taxes makes the defecit worse. Suggests the Federal Government reduce spending rather than raise taxes.